2011
DOI: 10.1016/j.geomphys.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of the two-component Camassa–Holm and Degasperis–Procesi equations

Abstract: Abstract. We use geometric methods to study two natural twocomponent generalizations of the periodic Camassa-Holm and Degasperis-Procesi equations. We show that these generalizations can be regarded as geodesic equations on the semidirect product of the diffeomorphism group of the circle Diff(S 1 ) with some space of sufficiently smooth functions on the circle. Our goals are to understand the geometric properties of these two-component systems and to prove local well-posedness in various function spaces. Furth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 25 publications
0
58
0
Order By: Relevance
“…Several types of 2-component Camassa-Holm equations have been studied in [41][42][43][44][45][46][47][48][49][50][51]7]. Several types of 2-component Camassa-Holm equations have been studied in [41][42][43][44][45][46][47][48][49][50][51]7].…”
Section: Introductionmentioning
confidence: 99%
“…Several types of 2-component Camassa-Holm equations have been studied in [41][42][43][44][45][46][47][48][49][50][51]7]. Several types of 2-component Camassa-Holm equations have been studied in [41][42][43][44][45][46][47][48][49][50][51]7].…”
Section: Introductionmentioning
confidence: 99%
“…The DP equation belongs to the class of non-metric Euler equations [17,24]. An analogous geometric framework has been established for the 2CH equation without vorticity in [12,20] where the authors showed that it can be recast as a geodesic flow on the semidirect product Diff ∞ (S) C ∞ (S) equipped with the H 1 metric for the first component plus the L 2 metric for the second component.…”
Section: Introductionmentioning
confidence: 99%
“…The 2DP was shown to have solitons, kink, and antikink solutions [57]. Escher, Kohlmann and Lenells studied the geometric properties of the 2DP and local well-posedness in various function spaces [19]. However, peakon and superposition of multi-peakons were not investigated yet.…”
Section: Introductionmentioning
confidence: 99%